Penerapan Model Pembelajaran Project Based Learning Berbantuan Media Visual Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Inpres Bontomanai - Andi Agus Nandi Putra Pradana; Muhammad Nawir; Fitri Yanty Muchtar (STIKes Ibnu Sina Ajibarang, 2023)
The main problem in this study is how to apply the Project Based Learning learning model to improve student learning outcomes for social studies learning in class V SD Inpres Bontomanai. This study aims to improve student learning outcomes in Social Studies learning with the Project Based Learning learning model in class V SD Inpres Bontomanai. This type of research is Class Action Research which consists of two cycles where each cycle is carried out as many as 3 (three ) meeting times. The research procedures included planning, carrying out actions, observing and reflecting. The subjects in this study were 25 students of grade V SD Inpres Bontomanai. The results showed that in the first cycle that was completed individually out of 25 students only 10 students or 40% fulfilled completeness. student learning outcomes on social studies learning. Classically it is not sufficient enough because the average value is 65. Whereas in cycle II where out of 25 students there are 19 students or 76% completeness of student learning outcomes on social studies learning and classically it has been fulfilled, namely the average value is 75.80 or is in the very good category. Based on the results of this study, it can be concluded that student learning outcomes on social studies learning using the Project Based Learning learning model in class V SD Inpres Bontomanai have increased.